PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SCRATCH UNTUK MENINGKATKAN INTERAKTIVITAS PEMBELAJARAN INFORMATIKA PADA SISWA SMP - Subekti, Lutfi; Suswanto, Hary; Kurniawan, Rachman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Informatics learning in Data Analysis materials in junior high schools is still dominated by the teacher-centered learning approach, so students tend to depend on teachers and lack opportunities to learn independently. This research aims to develop Scratch-based interactive learning media that is suitable to be used to support student-centered learning. The research uses the Research and Development (R&D) method with a 4D development model which includes the define, design, develop, and disseminate stages. The research was carried out at SMP Negeri 8 Malang with the subject of 30 grade VII students. The research instrument consisted of a questionnaire of students' dependence on teachers, a validation sheet of material experts, and a validation sheet of media experts. Data analysis was carried out using descriptive statistics with percentage techniques. The results of the needs analysis showed that the level of student dependence on teachers was 82%. The validation results obtained a percentage of 86% from subject matter experts and 92% from media experts, with an overall average of 89% which belongs to the very valid category. The results of the trial show that the media is able to increase engagement, learning independence, and make it easier for students to understand Data Analysis material through animations, interactive exercises, and direct feedback. Thus, Scratch-based learning media is declared feasible to be used as an alternative to Informatics learning that supports the implementation of student-centered learning